A comparative economic study of two configurations of hydro-wind power plants. (1st October 2016) - Bayón, L.; Grau, J.M.; Ruiz, M.M.; Suárez, P.M.
Abstract: This paper presents a comparison between two options for operating a wind park in combination with a pumped-storage hydro-plant. First, we analyze the behavior of a wind farm that goes to the electricity market having previously forecasted the wind speed, while accepting the deviation penalties these forecasts may incur. Second, we study the possibility of the wind farm not going to the market individually, but as part of a hydro-wind power plant. Considerations about the optimal size of the wind farm and the hydro-pumped storage plant have previously been analyzed in the literature. However, most of these papers do not analyze dynamic considerations. The dimensioning of the system is not studied in our paper; its main feature will instead be the consideration of the dynamic optimal control problem. The use of Pontryagin's Maximum Principle allows us to obtain a very efficient optimization algorithm. The hydro-plant is modelled in great detail, using a variable-head model for the pumped hydro-plant. Our study provides a useful tool for electricity companies. The algorithm is able to solve the problem of the day-ahead market, a problem that is not solved in other studies. Highlights: We present an optimal control study of the hydro-power pumping stations. We have presented two configurations for the combined hydro-wind power plant. We compare these two configurations in numerical simulations. We include the possible deviations in wind forecasting using an ARIMA model.